Impact of the oxbow lakes project II: on participant households - BRAC (© BRAC, 2016)
1. Introduction and background 2. Objectives 3. Proposals 4. Operational strategy 5. Implementation of the project 6. Crops and varieties 7. Marketing 8. Economic feasibility 9. Female participation